Knowledge Effect in Improvement Teamwork: Survey Study at Iraqi State Iron Roads Company (Al-Mansour Journal, 2022)
This Study Deals With one important subject in organization’s success, develop and the organization capability to competitors with the other organizations for growth and continues, we study knowledge effect on grouping work improvement. It’s used as one of styles work in the many organizations. The applied side of this study contains survey study to opinion for simple of the workers in state company of the iron roads. The data collect by questioner, this contents 20 questions to evaluate the knowledge effect in grouping work improving and analyze this data by using SPSS. Well introduce some results and recommendations to improving the grouping work